(untitled)
In this paper, we obtain the boundedness for the commutators of n-dimensional Hardy-type operators from mixed Herz spaces to weak mixed Herz spaces, where the symbol functions are in the intersection of the mixed central bounded mean oscillation space CBMO_q’ (R^n) and the weak mixed central bounded mean oscillation space W_q (R^n). , number=4, journal=Analysis in Theory and Applications, year=2026, month=Jan., pages=469–478